THEME: WRITING AND READING IN AN INTENSIVE LANGUAGE PROGRAM - Alovuddinova Sevara; Jamolova Shahina; Safarova Dildora (Ustozlar uchun, 2025)
Intensive language programs require a strong focus on both writing and reading skills to achieve rapid proficiency. Writing helps learners develop critical thinking, grammatical accuracy, and creativity, while reading enhances vocabulary, comprehension, and cultural understanding. The integration of these skills through structured activities, authentic materials, and feedback-based learning fosters better language acquisition. This article explores strategies for improving writing and reading, the role of instructors, and the importance of tailored curricula. Effective engagement in both skills ensures students gain fluency and confidence in the target language.